Work-Life Balance and Its Impact on Employee Performance (Maneggio, 2026)
The development of the modern work environment characterized by high flexibility, intense performance demands, and the use of digital technology has blurred the boundaries between employees' work and personal lives. This condition places work-life balance as a strategic issue in human resource management. This study aims to analyze the meaning of employees towards work-life balance, the dynamics of its application in the organizational environment, and its implications on employee performance. The research approach used is qualitative with a descriptive-exploratory design. Data was collected through semi-structured in-depth interviews with purposively selected employees, supported by organizational observations and documentation. Data analysis was carried out using thematic analysis to identify key patterns and themes that emerged from the informant's experience. The results of the study show that work-life balance is understood as the ability to control the demands of work roles and personal life in harmony. The implementation of work-life balance is influenced by organizational policies, supervisory support, workload, and the prevailing work culture. Employees who experience work-life balance show more stable levels of motivation, focus, and performance quality, while imbalances trigger burnout and decreased performance. These findings confirm that work-life balance plays an important role in maintaining the sustainability of employee performance. This research provides practical implications for organizations in designing human resource policies that are oriented towards long-term well-being and performance